The relationship between perceptions of school climate and internet gaming disorder of teenage students: A moderated mediation model - Zhang, Mengrou; Zhang, Wenhua; Li, Yunhe; He, Xiangcai; Chen, Feng; Guo, Ying (Frontiers in Psychology, 2022)
Background: In recent years, teenager students’ internet gaming disorder has raised widespread concern in the society. The current study aims to explore how school climate, maladaptive cognition and belief in a just world impact teenager students’ internet gaming disorder and seek the suitable intervention way to prevent teenager students’ internet gaming disorder tendency. Methods: 1164 teenager students were evaluated with the Perceived School Climate Scale, Maladaptive Cognition Scale, Belief in a Just World Scale, and Internet Gaming Disorder Scale. Results: (1) The school climate could predict teenager students’ internet gaming disorder. (2) Teenager students’ maladaptive cognition exerts a partial mediating effect between their school climate and internet gaming disorder. (3) The direct effect of school climate on internet gaming disorder, the first half of the mediation model “school climate → maladaptive cognition” and the second half of the mediation model “maladaptive cognition → internet gaming disorder” are all moderated reciprocally by teenager students’ belief in a just world. Conclusion: Schools should create a good climate and shape belief in a just world to reduce the maladaptive cognition of teenager, to effectively prevent teenager students’ internet gaming disorder tendency.